Pentingnya Kemampuan Berpikir Kritis dalam Dunia Pendidikan Matematika - Handayani Budi Utami (J-PiMat : Jurnal Pendidikan Matematika, 2022)
Mathematical critical thinking ability is one of the most needed skills in the modern era. Given the importance of critical thinking skills, education has an important role in improving critical thinking skills. This article will discuss critical thinking, the importance of critical thinking skills, especially in the mathematical aspect, as well as the efforts made to develop critical thinking skills. The writing of this article uses the literature review method. From the results of the study, critical thinking is based on skills, such as the ability to judge the truth, or to weigh relevant evidence, or to identify erroneous arguments. Critical thinking skills are important elements that must be possessed by students in analyzing mathematical problems. Given the important role of critical thinking today, many efforts have been made to improve critical thinking skills.